Architecture of Populism: Online Media and the Rise of Popular Common Politicians in Indonesian Political Landscape - Devie Rahmawati; Geger Riyanto; Deddy Mulyana; Mila Viendyasari; Wiratri Anindhita (Proceedings, 2023)
Populist figures were anything but a new phenomenon in Indonesian politics albeit in its short history as a modern state. However, in accordance with the recent development of news dissemination technology, the pattern of populist figure emergence was transformed. Not only in recent years we saw a considerable number of politicians, especially heads of local governments and ministers, attaining public popularity in ways unthinkable within the past political landscape. It is also unpredictable that the current president, who hardly had any strong political establishment, would rise into a legitimate candidate in the 2014 election without being underpinned by a novel and peculiar pattern of information and news circulation. This research aims to unravel the relationship between the current online media regime and the emergence of such populist figures. Additionally, as we follow the online news editorial process, we realized that we would not come to a satisfying conclusion, given that we disregard the materiality of the new media. Therefore, communication and media scholars should consider the importance of the agency of things, a conceptual apparatus proposed by scholars of Actor-Network Theory (ANT).